THE IMPLEMENTATION OF COLLATERAL IN THE CON-TRACT OF MUDHARABAH FINANCING ACCORDING TO ACT NO. 21 OF 2008 ON SHARIA BANKING AND DSN-MUI’s FATWA - Harahap, Mhd. Yadi (UI Scholars Hub, 2021)
Contract of mudharabah financing is principally intended to meet the interests of businesses in terms of capital or additional capital to implement a productive business, between two or more parties. The problems of contract of mudharabah financing arises when owners of capital requires collateral to be met by businesses. Imposition guarantees in classical fiqh that developed by the mazhab of Imam that in terms of mudharabah financing, capital owners cannot demand collateral from businesses to recoup the principal or capital plus profit. If the owners of capital require the provision of collater-al from mudharib and make collateral as a condition of a contract then the cooperation contract is null and void according to Maliki and Shafi’i. According to the Hanbali, and Abu Hanifah, only the conditions were null and void, while contract itself remains valid. In general, according to Law No. 21 Year 2008 on sharia banking, collateral is termed by rahn and kafalah. This is in line with the DSN-MUI Fatwa formulating collateral consists of Rahn and kafalah. It should be understood that the contract of mudharabah financing is different from the concept of financing debts that require no collateral. When syariah banking is applying guarantee in the contract of mudharabah financing, it will lead to another problem that is interest to be discussed. This research applies a legal normative method by approach legislations and Fatwa DSN-MUI, this allows the researcher to find the answer about the problems that are considered correct.